Resource Requirements for Nuclear Power Infrastructure Development. (IAEA nuclear energy series ;, 2022)
"Developing a nuclear power programme is a major undertaking requiring careful planning and preparation. This publication provides guidance for Member States that with to assess the resources required for the development of the infrastructure needed for a nuclear power programme. Resource estimates are presented in person years, to account for economic differences across countries, in terms of labour costs, which may vary significantly. The data are presented in sufficient detail that they can also be used by countries that have decided to expand their nuclear programme after a long period without building any new nuclear power plants."--Publisher's description.